2014
DOI: 10.1186/2047-2994-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a multimodal hand hygiene campaign and obstacles to success in Addis Ababa, Ethiopia

Abstract: BackgroundHand hygiene is the cornerstone of infection control and reduces rates of healthcare associated infection. There are limited data evaluating hand hygiene adherence and hand hygiene campaign effect in resource-limited settings, especially in Sub-Saharan Africa. This study assessed the impact of implementing a World Health Organization (WHO)-recommended multimodal hand hygiene campaign at a hospital in Ethiopia.MethodsThis study included a before-and-after assessment of health care worker (HCW) adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 20 publications
7
59
2
Order By: Relevance
“…Compliance at baseline was similar to two studies that had been undertaken in Ethiopia [19, 20] but was lower compared to a study from Bamako, Mali [21]. The main reason for the low baseline compliance appears obvious: hand hygiene products and facilities were not available on the wards.…”
Section: Discussionsupporting
confidence: 71%
“…Compliance at baseline was similar to two studies that had been undertaken in Ethiopia [19, 20] but was lower compared to a study from Bamako, Mali [21]. The main reason for the low baseline compliance appears obvious: hand hygiene products and facilities were not available on the wards.…”
Section: Discussionsupporting
confidence: 71%
“…28 These strategies have yielded short-term success, 29,30 but the longer-term impact has been negligible with rapid returns to baseline often displayed. 31 As multi-modal HH campaigns can sustain improvements most effectively, 12,14,32 involving patients in such endeavours could yield longer-term benefits. 14,33 Additionally, involving patients would enable continuous monitoring of HCPs' HH practices without the need for additional staff or resources.…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated poor tolerability of the WHO-recommended formulation of hand sanitizer and identi ed it as a barrier of hand hygiene (11). However, in this study we demonstrated a high demand for locally produced ABHS to combat the pandemic which is a key sign of acceptability during outbreaks.…”
Section: Discussion: Impact and Lessons Learntmentioning
confidence: 68%